2013
DOI: 10.4081/cp.2013.e32
|View full text |Cite
|
Sign up to set email alerts
|

Leiomyoma of the Seminal Vesicle: A Rare Case

Abstract: Leiomyomas though common benign tumors of smooth muscle cells are extremely rare in the male genitourinary tract. We present a case of an elderly male who presented with complaints suggestive of urinary bladder outlet obstruction since 1 year. His evaluation showed it due to a tumour arising from the left seminal vesicle. Excision of the tumor was done which was diagnosed on histopathology as leiomyoma. A brief case report and review of literature is being presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…Magnetic resonance imaging (MRI) revealed a mass of low and isointensity signals compared with soft tissue on T1-weighted imaging and low, moderately high, and isointensity signals on T2-weighted imaging 7 2009 Inan [ 9 ] Turkey 74 Asymptomatic 1.2 Left Transrectal biopsy leiomyoma No record The lesion was homogeneously hypo-intense on T2-weighted images and isointense on T1-weighted images homogeneous. After I.V contrast injection, the lesion enhanced strongly and homogeneously 8 2013 Shaikh [ 10 ] India 63 Lower urinary tract symptoms 5.7 × 5.1 Left Transrectal biopsy leiomyoma Laparoscopic excision MRI showed the presence of a retroperitoneal and retrovesical solid mass 9 2014 Miyajima [ 11 ] Japan 65 Lower abdominal disobedience 9.3 × 4.4 Right Transrectal biopsy leiomyoma Laparotomy through a lower midline incision CT showed oval plump tumor without contrast effect. MRI showed that the tumor was depicted with the same low signal as muscle in T1 and T2 stressed images.…”
Section: Discussionmentioning
confidence: 99%
“…Magnetic resonance imaging (MRI) revealed a mass of low and isointensity signals compared with soft tissue on T1-weighted imaging and low, moderately high, and isointensity signals on T2-weighted imaging 7 2009 Inan [ 9 ] Turkey 74 Asymptomatic 1.2 Left Transrectal biopsy leiomyoma No record The lesion was homogeneously hypo-intense on T2-weighted images and isointense on T1-weighted images homogeneous. After I.V contrast injection, the lesion enhanced strongly and homogeneously 8 2013 Shaikh [ 10 ] India 63 Lower urinary tract symptoms 5.7 × 5.1 Left Transrectal biopsy leiomyoma Laparoscopic excision MRI showed the presence of a retroperitoneal and retrovesical solid mass 9 2014 Miyajima [ 11 ] Japan 65 Lower abdominal disobedience 9.3 × 4.4 Right Transrectal biopsy leiomyoma Laparotomy through a lower midline incision CT showed oval plump tumor without contrast effect. MRI showed that the tumor was depicted with the same low signal as muscle in T1 and T2 stressed images.…”
Section: Discussionmentioning
confidence: 99%
“…Leiomyomas can proliferate in any tissue composed of smooth muscle and separated by any amount of connective tissue. According to some studies, leiomyoma originates from the Wolffian and Müllerian ducts, and the immunohistochemical differentiation remains controversial ( 9 ) .…”
mentioning
confidence: 99%
“…The most common changes to seminal vesicles are agenesis and cystic anomalies. Primary seminal vesicle neoplasms, which are extremely rare, include leiomyoma, cystadenoma, angioendothelioma, teratoma, schwannoma, and paraganglioma ( 9 , 10 ) . Patients with seminal vesicle leiomyoma are often asymptomatic, although lumbar pain, polyuria, dysuria, perineal pain, and infertility may occur ( 11 ) .…”
mentioning
confidence: 99%
See 1 more Smart Citation